Mechanistic aspects of plant-based silver nanoparticles against multi-drug resistant bacteria. Issue 7 (July 2021) - Wahab, Shahid; Khan, Tariq; Adil, Muhammad; Khan, Ajmal
Abstract: Resistance among pathogenic bacteria to the existing antibiotics is one of the most alarming problems of the modern world. Alongwith reducing the use of antibiotics, and antibiotic stewardship, an alternative to antibiotics is much needed in the current scenario to combact infectious diseases. One alternative is to produce nanomaterials, especially, silver nanoparticles (AgNPs) against antibiotic-resistant bacteria. AgNPs are the most vital and fascinating nanoparticles because of their unique structural and functional properties and application against pathogenic bacteria. However, the synthesis of AgNPs remains a problem because of the chemicals and energy requirements and the byproducts of the reactions. Concerns have been raised about using chemically and physically synthesized nanoparticles because of their potential risks to the human body, animals, and environment. Green synthesis of these nanoparticles is a better alternative to physical and chemical approaches. Plant-based synthesis in turn is a method which can provide AgNPs that are cost-effective and eco-friendly as well as biocompatible. The specific features of size, morphology and shape of plant-based AgNPs give them the potency to fight multi-drug resistant bacteria. A detailed look into mechanistic aspects of the action of AgNPs against resistant bacteria with a focus on characteristic properties of AgNPs is required. This review discusses in detail these aspects and the potential of plant-based AgNPs as a solution to antibiotic resistance. Abstract : Biogenic silver nanoparticles; Multi-drug resistant bacteria; Natural extracts.